Intra-Abdominal Venous Pressure During Laparoscopic Cholecystectomy. Issue 1 (1994) - Iwase, Kazuhiro; Takao, Tetsuto; Watanabe, Hirotoshi; Tanaka, Yasuhiro; Kido, Tetsuo; Ogawa, Noritusugu; Ono, Norio; Yoshitake, Hiroshi
Abstract : Superior vena cava (SVC) and inferior vena cava (IVC) pressures were measured serially during laparoscopic cholecystectomy in which the intra-abdominal pressure was maintained at 12mmHg. The influences of alteration of position from 15 degrees head-down to 15 degrees head-up and of the operative procedure of holding the gallbladder up to the right subphrenic space on SVC and IVC pressures were mild. IVC pressure was maintained almost equal to the intra-abdominal pressure during prolonged continuous pneumoperitoneum lasting longer than 60min, while SVC pressure did not change significantly during operation. The discrepancy between SVC and IVC pressures underwent no change during continuous pneumoperitoneum.